Exploring the Health Benefits of Matcha: A Comprehensive Review - Korn, Aleksandra; Jędrzejczyk, Justyna; Łopacińska, Olga; Stańczyk, Katarzyna; Czarnecka, Karolina; Wójcik, Emilia; Korczak, Anna; Szewczyk, Oliwia; Olek, Ewa; Burda, Katarzyna (Journal of Education, Health and Sport, 2024)
Introduction: Matcha, a finely powdered form of green tea, has recently gained global popularity due to its vibrant green color, distinctive taste, and versatile applications in various food products. Despite its promising nutritional profile, matcha has not received significant attention in the academic community compared to traditional green tea. Purpose of work: The primary objective of this review is to provide a comprehensive overview of the current understanding of matcha's biological properties and its potential health benefits. Methods and materials: A review of the literature available in the PubMed database and Google Scholar, the following keywords were searched: "matcha", “catechin", "EGCG", “cognitive function”, “green tea” State of knowledge: Existing studies have demonstrated that matcha exhibits anticancer properties, enhances cognitive function, improves cardio-metabolic health, and modulates the gut microbiome. Moreover, matcha is known for its anti-inflammatory and antioxidant properties. Summary: This review summarizes the latest research findings on matcha green tea and its potential health benefits. While animal studies have shown promising results, our knowledge of matcha's effects on human health remains limited. Further randomized controlled trials are necessary to fully elucidate its potential health-promoting effects. Therefore, we advocate for continued research into matcha's properties and its integration into dietary practices to promote overall health and well-being.